2019
DOI: 10.1371/journal.pmed.1002985
|View full text |Cite
|
Sign up to set email alerts
|

Duration of type 2 diabetes and remission rates after bariatric surgery in Sweden 2007–2015: A registry-based cohort study

Abstract: BackgroundAlthough bariatric surgery is an effective treatment for type 2 diabetes (T2D) in patients with morbid obesity, further studies are needed to evaluate factors influencing the chance of achieving diabetes remission. The objective of the present study was to investigate the association between T2D duration and the chance of achieving remission of T2D after bariatric surgery.Methods and findingsWe conducted a nationwide register-based cohort study including all adult patients with T2D and BMI ≥ 35 kg/m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 34 publications
6
65
2
2
Order By: Relevance
“…In terms of T2D remission at 1 year, the present study observed 42.2% complete remission and 18.8% partial remission rates. Both these levels were lower than those reported by other authors (66.2%-79.1% complete remission, 11.9% partial remission) [24][25][26]. Such variations in remission rates are probably because of the heterogeneity of definitions of T2D remission employed by various studies [6,8,16].…”
Section: Discussionmentioning
confidence: 60%
“…In terms of T2D remission at 1 year, the present study observed 42.2% complete remission and 18.8% partial remission rates. Both these levels were lower than those reported by other authors (66.2%-79.1% complete remission, 11.9% partial remission) [24][25][26]. Such variations in remission rates are probably because of the heterogeneity of definitions of T2D remission employed by various studies [6,8,16].…”
Section: Discussionmentioning
confidence: 60%
“…Increasing age, dyslipidaemia, T1DM, and previous acute coronary events were all associated with lower chances of achieving remission of hypertension. As with remission of T2DM, patients with shorter duration of disease and those losing more weight had a higher chance of remission [37].…”
Section: Plos Medicinementioning
confidence: 98%
“…122 One study found that remission of T2DM after bariatric surgery was achieved in 58.2% (n = 2090) of patients at 2 years, and in 46.6% of patients at 5 years. 125 Although T2DM remission can be as high as 74% at 1 year postsurgery, T2DM relapse increased over time with a longer follow-up duration. 125,126 As summarized earlier, TTh for 8 years results in weight loss corresponding to 16.8% to 23.6%, depending on baseline obesity grade (Table 1).…”
Section: Tth In Comparison To Bariatric Surgerymentioning
confidence: 96%
“…125 Although T2DM remission can be as high as 74% at 1 year postsurgery, T2DM relapse increased over time with a longer follow-up duration. 125,126 As summarized earlier, TTh for 8 years results in weight loss corresponding to 16.8% to 23.6%, depending on baseline obesity grade (Table 1). 55 An 11-year a References.…”
Section: Tth In Comparison To Bariatric Surgerymentioning
confidence: 96%